Geochronology of the Tore-Madeira Rise seamounts and surrounding areas: a review - Merle, Renaud; Jourdan, Fred; Girardeau, J. (Taylor & Francis Co Ltd, 2018)
© 2018 Geological Society of Australia We present new 40 Ar/ 39 Ar data for two of the Tore-Madeira Rise (TMR) volcanic seamounts. A sample from Tore East seamount on the northern part of the TMR yielded an ultra-precise age of 80.50 ± 0.13 Ma (2s) that is similar within uncertainties to a published age obtained by U–Pb TIMS technique on titanites and zircons extracted from Tore NW seamount. Another sample from Isabelle seamount, located on the southern part of the TMR failed to produce a plateau age but yielded a minimum age estimate of > 85 Ma. We filtered the published ages available on the TMR, the surrounding seamounts and the massifs of southwest Portugal to better understand the origin of this magmatic province. Together with this dataset, our new data suggest that:(1) a hypothetical Madeira hot-spot track spanning from Serra de Monchique on the continent to Madeira Archipelago is difficult to reconcile with the occurrence of several seamounts geographically located within or very close to this alleged hot-spot track yet being much older than the age predicted by the age trend.(2) The geographical distribution and age pattern of the TMR and surrounding areas magmatism are still best explained by the interaction of a mantle melting anomaly emitting magma pulses and the different motion phases of the Iberia plate since 103 Ma.